In vitro anti-inflammatory activities of blacklip abalone (Haliotis rubra) in RAW 264.7 macrophages. Issue 4 (4th July 2017) - Suleria, Hafiz Ansar Rasul; Addepalli, Rama; Masci, Paul; Gobe, Glenda; Osborne, Simone A.
ABSTRACT: Abalone ( Haliotis sp ) has been used as a traditional functional food for many years by different cultures believing that consumption provides health benefits. We investigated the anti-inflammatory activity from blacklip abalone visceral waste. An extract was prepared from the viscera using digestion with the food grade proteases papain and bromelain followed by anion exchange chromatography (AEC). The anti-inflammatory potential of the extract and AEC fractions were investigated in comparison to a plant-derived positive control (quercetin) through the inhibition of lipopolysaccharide-stimulated nitric oxide production in RAW 264.7 monocytes. Significant anti-inflammatory activity was observed in response to the abalone extract and the unbound AEC material over a concentration (based on collagen) range of 12–96 µg/mL. Overall, results indicated that blacklip abalone extract has anti-inflammatory activity in vitro, warranting further investigation into the bioactive constituents that may be potential anti-inflammatory therapeutics.